Musculoskeletal disorders in final year students of the Dentistry Career at the Catholic University of Cuenca - Martínez Hernández, Juan Carlos (2021)
TMJ´s are contained within the ILO list of occupational diseases and are defined as the pathological state that manifests itself suddenly or by slow evolution as a result of the work process, they cause 1.7 million deaths annually. Objetivo. Analyze the postures of dental students during their clinical practice. Materials and Methods. 51 students belonging to the tenth cycle were randomly chosen to analyze the postures adopted during clinical practice through photography using the REBA methodology. The data were analyzed in SPSS software. Results. 98% of the students twist and flex their wrist to use the dental turbine. After the REBA analysis, it was observed that 64.6% of the students present a medium risk level, 29.3% present a high risk level and 5.9% present a low risk level. Conclution. There are positions that are typical of the dental profession and that could lead to the development of TME in dental professionals, this added to the ignorance of principles in ergonomics makes it necessary to educate and train students during their university preparation, which would favor maintain your health during the exercise of your profession.